2015
DOI: 10.1016/j.physa.2015.02.098
|View full text |Cite
|
Sign up to set email alerts
|

Complementary action of chemical and electrical synapses to perception

Abstract: Abstract. We study the dynamic range of a cellular automaton model for a neuronal network with electrical and chemical synapses. The neural network is separated into two layers, where one layer corresponds to inhibitory, and the other corresponds to excitatory neurons. We randomly distribute electrical synapses in the network, in order to analyse the effects on the dynamic range. We verify that electrical synapses have a complementary effect on the enhancement of the dynamic range. The enhancement depend on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…To elucidate the fundamental dynamical mechanisms behind observable brain behaviour, there has been a lot of research based on simulations of neuron networks and their behaviour as a function of the intensity of the coupling strengths 13 14 15 16 17 18 19 20 and the connecting topology 21 22 23 24 . Under strong coupling strengths, neuron networks of equal neurons support the appearance of complete synchronisation (CS) 17 18 19 20 , as shown in Fig.…”
mentioning
confidence: 99%
“…To elucidate the fundamental dynamical mechanisms behind observable brain behaviour, there has been a lot of research based on simulations of neuron networks and their behaviour as a function of the intensity of the coupling strengths 13 14 15 16 17 18 19 20 and the connecting topology 21 22 23 24 . Under strong coupling strengths, neuron networks of equal neurons support the appearance of complete synchronisation (CS) 17 18 19 20 , as shown in Fig.…”
mentioning
confidence: 99%
“…The increase of the DR value is also associated with the increase of the number of excitatory chemical synapses [12,13]. Borges et al [14] reported the complementary effect of chemical and electrical synapses on the enhance of the DR. Protachevicz et al shown that chemical synapses can enhance DR of the neural network submitted to external stimuli [15].…”
Section: Introductionmentioning
confidence: 98%
“…In this work, we investigate the criticality and dynamic range of a cellular automaton modelling a neuronal network in which the neurons are connected by means of excitatory and inhibitory chemical synapses [12,14]. In order to understand the relationship between maximisation of the DR and the critical self-sustainable activity, we consider a refractory period in the model like the one proposed by Larremore et al [32].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, neural network models have been used extensively in neuroscience applications, such as in studies of neural dynamics 5 , dynamic range [6][7][8][9] , neural synchronization [10][11][12][13][14] , flow of information [15][16][17] and brain plasticity 18,19 to name a few.…”
Section: Introductionmentioning
confidence: 99%